What Can Patient Narratives Reveal to Us About the Experience of a Diagnosis of Myeloma? A Qualitative Scoping Review. (February 2022) - Rubins, Zoë; Gibson, Barry J; Chantry, Andrew
In recent years, there have been major advances in treatment options for myeloma and an improved prognosis as a result. There is a wealth of literature that explores the experience of specific treatments from a clinical perspective but there is comparatively little known about the reality of living with myeloma. This research aims to explore the experience of a myeloma diagnosis, to map out key patient experience literature, and examine common themes to support both medical practice and the planning of further research. Following a scoping review methodology, PubMed, StarPlus (the University of Sheffield online database), and Scopus were searched and 15 studies identified for analysis and qualitative synthesis. The literature indicated that myeloma was increasingly being experienced as a chronic condition rather than an acute diagnosis and that there are challenges meeting the needs of patients, understanding the overall symptom burden and the role of the family. The paper identifies emotional and psychological adjustment and coping as a potential area requiring further exploration in the context of a whole team approach to care.